Structural basis of human cytomegalovirus neutralization by gB AD-5-specific potent antibodies - Changwen Wu; Nan Song; Yizhen Zhao; Han Wang; Yuanbao Ai; Yayu Wang; Yueming Wang; Xiaohui Yuan; Tong Liu; Nan Li; Dabbu Kumar Jaijyan; Chengming Li; et al. (Cell Reports)
Summary: Human cytomegalovirus (hCMV) poses a severe threat to fetuses, newborns, and immunocompromised individuals. No approved vaccines and limited treatment options are current medical challenges. Here, we analyze the human B cell responses to glycoprotein B (gB) in three top hCMV neutralizers from a cohort of 283 individuals with latent-infected hCMV. By single-cell amplification of memory B cells, we identify a cluster of potent neutralizing monoclonal antibodies (nAbs) that competitively recognize an unknown vulnerable site on gB antigenic domain 5 (AD-5). This cluster of nAbs functionally outperforms the nAbs utilized in clinical trials. Cryoelectron microscopy (cryo-EM) unveils the structural basis of the neutralization mechanism of an antibody directly targeting the fusion subdomain on AD-5. Moreover, immunological analyses of human and mouse sera have preliminarily validated the potential superiority of AD-5-focused immune responses. Overall, our results will support the development of optimized gB-based vaccines and provide promising prophylactic and therapeutic antibody candidates against hCMV infection.